Novedades y comentarios para la orquidoflora centro-occidental ibérica - Bernardos, Sonia; Amich García, Francisco (Lazaroa, 2000)
Bernardos, S. & Amich, F. New localities and remarks on the taxonomy of middle-western Iberian orchids. Lazaroa 21: 1318 (2001). Floristic, taxonomic, chorological and phytosociological data on 8 middle-western Iberian orchids (from Salamanca, Spain, and TrasOs-Montes, Portugal) are provided. Two are new records for northern Portugal and the remainder are new for the middle-western region, for a province or represent a significant enlargement of the known distribution area. Chromosome numbers for several species are also given for the first time for material from the Iberian Peninsula. cuadre fitosociológico de algunas de estas especies